Clinical significance and reversibility of abnormal spirometry in patients undergoing transcatheter aortic valve implantation - Ahmet Anıl Başkurt; Mutlu Onur Güçsav; Mesut Özkahya; Yusuf Demir; Çağla Aktürk Çelik; Abdullah Kadir Dolu; Ahmet Erseçgin; Ferhat Siyamend Yurdam; Oktay Şenöz; İlker Gül (Medical Journal of Western Black Sea, 2026)
Aim: Abnormal spirometry is frequently observed during pre-procedural evaluation of patients with severe aortic stenosis undergoing transcatheter aortic valve implantation (TAVI). However, such findings may reflect hemodynamically mediated pulmonary congestion rather than true chronic pulmonary disease. To evaluate the prevalence, clinical significance, and reversibility of abnormal spirometry in patients with severe aortic stenosis undergoing TAVI without established pulmonary disease.Material and Methods: This prospective observational study included patients with severe aortic stenosis who underwent TAVI between 2020 and 2026. Patients with known chronic pulmonary disease or atrial fibrillation were excluded. Based on baseline spirometry, patients were classified as having normal or abnormal pulmonary function. Clinical outcomes, including length of hospital stay and mortality, were compared between groups. Follow-up spirometry was performed in patients with abnormal baseline findings to assess reversibility.Results: Among 69 included patients, 30 (43.5%) had abnormal baseline spirometry, predominantly PRISm patterns (73.3%). Length of hospital stay and in-hospital or follow-up outcomes were similar between patients with normal and abnormal spirometry. At follow-up, patients with abnormal baseline spirometry demonstrated significant improvement in forced expiratory volume in one second and forced vital capacity (both p